Coexistence of fluoroquinolone resistance and ESBL production in urinary isolates - Khan, Nazia; Panda, Pragyan Swagatika; Rastogi, Megha; Sharma, Swati; Rana, Neha; Faridi, Maryam; Mehndiratta, Man Mohan (International Journal Of Community Medicine And Public Health, 2020)
Background: Enterobacteriaceae group of organisms are commonly implicated for causing urinary tract infection (UTI). Fluoroquinolones (FQ) are widely used as empirical therapy for UTI. Enterobacteriaceae exhibits high resistance rates to FQs. The plasmid mediated extended spectrum beta lactamase (ESBL) production confers resistance for FQs as well. The aim of the study is to determine the prevalence of fluoroquinolones resistance in urinary isolates and to study the coexistence of FQ resistance and ESBL production in urinary isolates. Methods: Retrospective data of the urine samples received in our microbiology laboratory between December 2018 to May 2019 were reviewed. The organisms were isolated and identified as per standard procedures and the antibiotic susceptibility testing was done following CLSI 2019 guidelines. Ceftazidime (30 µg) and ceftazidime-clavulinic acid (30 µg/10 µg) were used for detection of ESBL production. Levofloxacin (5 µg) and ciprofloxacin (5 µg) were used for detecting FQ resistance. Results: Out of a total of 1403 urine samples received in our laboratory, 240 (17.1%) sample showed growth of Enterobacteriaceae. The different species were E. coli (80.4%), Klebsiella spp (12.2%), Citrobacter spp (4.2%), Enterobacter spp (1.6%) and Proteus mirabilis (1.6%). Amongst these organisms 121(50.4%) were ESBL producers. Co-existence of FQ resistance among the ESBL producers was observed in 106(87.6%) isolates which is higher as compared to that among the ESBL non producers 71(59.7%). Conclusions: Around 50% of the UTI Enterobacteriaceae bacteria are ESBL producers. Fluroquinolone resistance amongst ESBL producing Enterobacteriaceae is very high (87.6%).